2000
DOI: 10.1038/sj.ijo.0801457
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of age, menopause and central obesity on cardiovascular disease risk factors in Chinese women

Abstract: OBJECTIVE: To evaluate the inter-relationships of age-and menopause-related changes of general obesity and body fat distribution and their independent effects on cardiovascular risk factors. DESIGN: Cross-sectional study. SUBJECTS: One-hundred and thirty-six premenopausal and 193 postmenopausal Chinese women with body mass index (BMI)`30 kgam 2 . MEASUREMENTS: Anthropometric surrogates of general obesity (BMI, total body fat percentage) and central obesity (waist-to-hip ratio, centrality index) were measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 34 publications
7
57
1
9
Order By: Relevance
“…2,20,31,34) that ovariectomy leads to a 14 -21% increase in weight within several weeks of ovariectomy. Also, it is well documented that along with weight gain, an increase in BMI and an increase in adiposity occur during the menopausal transition in women (18,39,52,64,67,103,113). Thus it is important to note that the monkeys in this study were ovariectomized.…”
Section: Discussionmentioning
confidence: 93%
“…2,20,31,34) that ovariectomy leads to a 14 -21% increase in weight within several weeks of ovariectomy. Also, it is well documented that along with weight gain, an increase in BMI and an increase in adiposity occur during the menopausal transition in women (18,39,52,64,67,103,113). Thus it is important to note that the monkeys in this study were ovariectomized.…”
Section: Discussionmentioning
confidence: 93%
“…Among these factors the android pattern of body fat distribution seems to be the major issue. The android body fat distribution, glucose intolerance, hyperlipidaemia and hypertension appear to be clustered together in the same subject 9 .…”
Section: Shahnila Ferdousimentioning
confidence: 99%
“…This has led to the postulation that obesity might be less harmful or even protective in old age (Al Snih et al 2007;Reis et al 2009;Auyeung et al 2010;Lea et al 2009). Yet, BMI is a measure of overall adiposity, which makes no distinction between fat elsewhere and abdominal fat, the latter being metabolically more harmful (Lapidus et al 1994;Chang et al 2000;Snijder et al 2006). Some have demonstrated that overall adiposity and abdominal adiposity act in different directions regarding the risk of metabolic diseases such as diabetes or cardiovascular diseases (Lapidus et al 1994;Lafortuna et al 2006).…”
Section: Introductionmentioning
confidence: 99%